Evidence in civil proceedings - Butryn-Boka, Nataliia; Botvynnyk, Viktoriia (Actual problems of law (Aktual'ni problemi pravoznavstva), 2020)
Peculiarities of proving in civil proceedings are investigated.  Particular attention is paid to innovations in the institute of civil evidence after amendments to the procedural codes of Ukraine in 2017.  Emphasis is placed on the relevance of this topic today. This topic has been considered by many scientists and is relevant today.  But still, I believe that there are many issues that need to be addressed at the scientific level.  In particular, the problem of electronic evidence needs to be solved the most, because the use of such evidence is a progressive innovation, which still requires consolidation of the procedure for their registration, submission and research. The object of the study was the procedural legal relationship to prove the circumstances that are decisive in civil cases.  In particular, the procedural actions of persons involved in civil proceedings are aimed at establishing the presence or absence of circumstances and facts necessary to resolve the dispute. The article reveals the essence of the concept of "proof" in civil proceedings and the purpose of this institution, which involves the establishment of objective truth.  Evidential facts and means of establishing evidence are considered in accordance with current legislation. In the course of scientific research, innovations in evidence in civil proceedings were identified, which are enshrined in judicial reform.  Among them are: expanding the list of means of proof, which provides for the separation of electronic evidence, the establishment of new requirements for evidence such as reliability and sufficiency, and so on. The analysis of problems that arise in the process of proving and need a legislative solution is also carried out.  One of them is the problem of the standard of proof in civil cases, which is related to the evaluation of evidence.